PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN DI KOPI KENANGAN CAB. RUKO NGAGEL ( STUDI KASUS PADA KONSUMEN DI SURABAYA TIMUR ) - Silvia Septiani; Nekky Rahmiyati (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the impact of price perception, product quality, and service quality on purchasing decisions and consumer satisfaction at Kopi Kenangan, Ruko Ngagel Branch, East Surabaya. With the increasing competition in the coffee industry in Indonesia, understanding the factors that influence purchasing decisions and consumer satisfaction is crucial for business sustainability. The population of this study consists of consumers who have made purchases at the Kopi Kenangan Ruko Ngagel Branch, with a sample taken through purposive sampling. Data were collected using questionnaires distributed to 100 respondents and analyzed using Structural Equation Modeling (SEM). The results show that price perception has a significant impact on purchasing decisions and consumer satisfaction. Product quality also has a positive effect on both variables, while service quality significantly influences both consumer satisfaction and purchasing decisions. Purchasing decisions were found to be a strong mediator between product quality, service quality, and consumer satisfaction. These findings imply that Kopi Kenangan management should pay more attention to price, product quality, and service aspects to enhance customer experience and strengthen customer loyalty.